Boosting the resolution of low-field 15 N relaxation experiments on intrinsically disordered proteins with triple-resonance NMR - Jaseňáková, Zuzana; Zapletal, Vojtěch; Padrta, Petr; Zachrdla, Milan; Bolik-Coulon, Nicolas; Marquardsen, Thorsten; Tyburn, Jean-Max; Žídek, Lukáš; Ferrage, Fabien; Kadeřávek, Pavel (Journal of biomolecular NMR, 2020)
Improving our understanding of nanosecond motions in disordered proteins requires the enhanced sampling of the spectral density function obtained from relaxation at low magnetic fields. High-resolution relaxometry and two-field NMR measurements of relaxation have, so far, only been based on the recording of one- or two-dimensional spectra, which provide insufficient resolution for challenging disordered proteins. Here, we introduce a 3D-HNCO-based two-field NMR experiment for measurements of protein backbone 15 N amide longitudinal relaxation rates. The experiment provides accurate longitudinal relaxation rates at low field (0.33 T in our case) preserving the resolution and sensitivity typical for high-field NMR spectroscopy. Radiofrequency pulses applied on six different radiofrequency channels are used to manipulate the spin system at both fields. The experiment was demonstrated on the C-terminal domain of δ subunit of RNA polymerase from Bacillus subtilis, a protein with highly repetitive amino-acid sequence and very low dispersion of backbone chemical shifts.
Keywords: DNA řízené RNA-polymerasy; Bacterial Proteins; rekombinantní proteiny; Dynamics; Intrinsically Disordered Proteins; vnitřně neuspořádané proteiny; nukleární magnetická rezonance biomolekulární; Recombinant Proteins; High-resolution relaxometry; Nuclear magnetic resonance; bakteriální proteiny; Intrinsically disordered proteins; Relaxation; Non-uniform sampling; Nuclear Magnetic Resonance, Biomolecular; DNA-Directed RNA Polymerases; Bacillus subtilis